2015
DOI: 10.1186/s12863-015-0241-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of markers with non-additive effects on milk yield and fertility in Holstein and Jersey cows

Abstract: BackgroundIt has been suggested that traits with low heritability, such as fertility, may have proportionately more genetic variation arising from non-additive effects than traits with higher heritability, such as milk yield. Here, we performed a large genome scan with 408,255 single nucleotide polymorphism (SNP) markers to identify chromosomal regions associated with additive, dominance and epistatic (pairwise additive × additive) variability in milk yield and a measure of fertility, calving interval, using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Significant inbreeding depression can also happen even without large dominance variances if the dominance deviations are small across many loci (Bolormaa et al, 2015). Aliloo et al (2015) implemented a large genome scan on milk yield and CaI with a similar data set to the one in the present study and found that the dominance effects of markers with suggestive dominance gene actions were very small and distributed all over the genome. This is in agreement with the findings of the present study where the effect of average heterozygosity on trait phenotypes was significant for all traits, but the dominance variance was not significant after correcting for average heterozygosity.…”
Section: Discussionmentioning
confidence: 81%
“…Significant inbreeding depression can also happen even without large dominance variances if the dominance deviations are small across many loci (Bolormaa et al, 2015). Aliloo et al (2015) implemented a large genome scan on milk yield and CaI with a similar data set to the one in the present study and found that the dominance effects of markers with suggestive dominance gene actions were very small and distributed all over the genome. This is in agreement with the findings of the present study where the effect of average heterozygosity on trait phenotypes was significant for all traits, but the dominance variance was not significant after correcting for average heterozygosity.…”
Section: Discussionmentioning
confidence: 81%
“…Only few studies have used the AD-model in GWAS to explicitly estimate a and d ( e.g. , Lopes et al 2014; Aliloo et al 2015; Huang et al 2015; Bennewitz et al 2017) and, to our knowledge, none have investigated differences in accuracy of estimated average effects between the A-model and AD-model. The effects of sampling genotypes on αtrue^ shown in this study apply to αtrue^m in GWAS, because αtrue^m are usually estimated by ordinary least squares.…”
Section: Discussionmentioning
confidence: 99%
“…Here, 435 unrelated poplar individuals, whose LD is much lower than animals, were used for identifying epistasis effects, which may reduce the false positive rate in our study. However, further work should be performed to validate the significant epistasis effects 35 . Also, genome-wide deep sequencing and computer analysis software will make SNP-based association genetics analysis more powerful for construction of GRNs.…”
Section: Discussionmentioning
confidence: 99%